Completion of first Beckman LS 9800 liquid scintillation instrument (1981)
Unidentified Beckman Instruments employees who worked on the LS 9800 liquid scintillation counter. Liquid scintillation counters measure the radioactivity of a sample by mixing the sample with a solvent containing a scintillator, which will emit photons in the presence of radioactive materials. The counter measures the pulses of photons as wavelengths of light detected through phototubes.
Keywords: Liquid scintillation counting; Employees; Scientific apparatus and instruments--Design and construction; Women employees; Beckman Instruments, Inc.